Artykuł oryginalnyPrevention of contrast-induced nephropathy in patients undergoing percutaneous coronary interventions in everyday clinical practice - Bachórzewska-Gajewska, Hanna; Małyszko, Jolanta; Sitniewska, Ewa; Małyszko, Jacek (Archives of Medical Science, 2006)
Introduction: Contrast nephropathy is a potentially serious complication of PCI, particularly in patients with chronic kidney disease – CKD. Material and methods: Assessment of the effects of preventive measures on the prevalence of contrast-induced nephropathy in 529 consecutive patients with coronary artery disease undergoing percutaneous coronary interventions. In all the patients 24 h before PCI all nephrotoxic drugs (NSAIDs, diuretics, biguanidine derivatives in diabetic patients) were withdrawn and doses of ACEi were either withdrawn or reduced. Results: Only 27.4-47.7% of patients with normal serum creatinine at admission had eGFR over 90 ml/min according to Cockcroft-Gault and MDRD formulae. In 39 patients we observed a rise in serum creatinine of more than 25% relative to baseline. More frequently they were females, hypertensive, PCI time was longer and contrast volume was higher. In 5 pts (0.9%) acute renal failure was observed (rise in creatinine more than 0.5 mg/dl relative to baseline). These patients received more contrast agent (p<0.01) and PCI was longer (p<0.01). In 21 patients we observed a significant fall in serum creatinine. They received significantly less contrast and low-osmolar contrast, and PCI was shorter. Estimated GFR and serum creatinine after PCI were not influenced by type of hydration (0.9% NaCl or 8.4% NaHCO3). Conclusions: Awareness of contrast nephropathy should be highlighted in primary care physician practice since some patients (with decrease in serum creatinine after PCI) were not well prepared for the procedure (mainly dehydrated). The prevalence of impaired renal function is relatively high in patients undergoing elective coronarography despite normal serum creatinine. The risk of contrast nephropathy is enhanced in these patients; therefore GRF should be estimated before coronarography. It is an inexpensive, reliable and widely available method. The most important prophylactic measure is adequate hydration, but low-osmolar contrast, contrast volume and duration of PCI should also be taken into account.